2011
DOI: 10.3184/095422911x12966667026105
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical distribution of heavy metals in sediments from sewage fed fish ponds from Kolkata Wetlands, India

Abstract: Kolkata wetlands are the largest sewage fed wetlands in the world. They have been used for aquaculture since 1960. Geochemical distribution of heavy metals (Cr, Cu, Mn, Fe, Zn, Pb, Ni and Al) has been studied in surface sediments using single and sequential extractions techniques. The metal concentrations in sediments were in the following order: Fe4Al4Mn4Zn4Cu4Pb4Cr4Ni, and the average concentrations were 29 mg g À 1 , 54 mg gdry weights for Cr, Cu, Mn, Fe, Zn, Pb, Ni and Al, respectively. Water-soluble perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 43 publications
0
10
0
2
Order By: Relevance
“…Manganese concentrations in this study were similar to those reported by Ahmed and Naim (2008) . Kumar et al (2011) recorded Mn concentrations (2.9 μg/g) in several fish species collected from Indian waters. A concentration of 0.5 mg/kg Mn in marine fish species gathered from Kochi Waters has been documented by Sankar et al (2006) .…”
Section: Discussionmentioning
confidence: 99%
“…Manganese concentrations in this study were similar to those reported by Ahmed and Naim (2008) . Kumar et al (2011) recorded Mn concentrations (2.9 μg/g) in several fish species collected from Indian waters. A concentration of 0.5 mg/kg Mn in marine fish species gathered from Kochi Waters has been documented by Sankar et al (2006) .…”
Section: Discussionmentioning
confidence: 99%
“…Though preventive measures have been taken to reduce the input of trace metals into oceans, rivers and estuaries, accumulation in the different aquatic systems have been reported even today (Kumar et al, 2010(Kumar et al, , 2011Dural and Bickici, 2010;Paller and Litterell, 2007). Industrial wastes and mining can create a potential source of heavy metal pollution in the aquatic environment (Gumgum et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Khosravi et al reported the high accumulation of this metal in Anzali wetland deposits [13]. Also according to Ashja Ardalan et al Zn and Pb concentrations in the deposits, water and soft tissues of Anadonta cygnea in the Anzali wetland was higher and lower than a Source: [41,42].…”
Section: Discussionmentioning
confidence: 99%